Preference of Bemisia tabaci MED (Hemiptera: Aleyrodidae) among morphologically and physically distinct tomato genotypes - dos Santos, Maria Clezia [UNESP]; da Silva Santana, Alisson; Schulz, Gabriela Pereira [UNESP]; Cabral, Isabella Rubio [UNESP]; dos Santos, Thais Lohaine Braga [UNESP]; Lourenção, André Luiz; Baldin, Edson Luiz Lopes [UNESP] (Springer Nature, 2023)
The recent introduction of Bemisia tabaci (Gennadius) MED (Hemiptera: Aleyrodidae) in the main tomato-producing areas in Brazil is concerning due to its high infestation capacity and to the numerous lethal viruses that this insect can transmit to plants. In addition, B. tabaci MED has a history of lower susceptibility to several groups of insecticides. Thus, this study evaluated the preference of B. tabaci MED among 39 tomato genotypes, belonging to seven Solanum species, as well as the physical and morphological factors related to the preference. The tomato genotypes LA 716, IAC 294, PI 127,826, PI 134,418, PI 134,417, Tainara, PI 126,925 and LA 116 expressed resistance to B. tabaci MED. The density of glandular trichomes was negatively correlated with the number of adults, B. tabaci MED eggs/cm² and nymphs/cm². On the other hand, the density of non-glandular trichomes and the slope of the trichomes stimulated the colonization by adults of B. tabaci MED. Substrate color was not correlated with genotype preference. The resistant genotypes and their characteristics can be explored in genetic breeding programs with the aim of developing cultivars resistant to whiteflies.
Keywords: Colorimetry; Glandular trichomes; Plant resistance; Solanum spp; Tomatoes; Whitefly biotype Q